Students’ Perception On Peer Correction For Academic Writing Performance - Chasna Tsuroyya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
Peer correction has taken an important role in language teaching and learning as in contribution to motivate the performance of L2 learners in writing classroom. Peer correction encourages the development of autonomous learning due to teachers' review that took over-dependence thus lowered the students' initiative. However, the previous studies show that many teachers are still doubting the effectiveness of peer correction because of students' lack of knowledge and unable to assist other students. The current study investigated the writing performance of English L2 learners who either provided or received written peer correction in the context of academic writing tasks. Fifteen participants enrolled in English Education Department in Universitas Sebelas Maret who are attending writing class were given a rubric to both reviews other students' writing tasks and receive peer feedback. Besides, we investigated whether students' peer correction perceptions influenced their writing performance. Results expect the use of peer correction to increase their writing motivation, self-regulated reflection, bidirectional communication, and deeper critical thinking. This study expects to provide a clear finding of the efficiency of peer correction in improving students' academic writing and can be useful to be implemented in writing class for English L2 learners.